2019
DOI: 10.1016/j.immuni.2019.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Glycan-Modified HIV NFL Envelope Trimer-Liposomes Elicits Broadly Neutralizing Antibodies to Multiple Sites of Vulnerability

Abstract: SummaryThe elicitation of broadly neutralizing antibodies (bNAbs) against the HIV-1 envelope glycoprotein (Env) trimer remains a major vaccine challenge. Most cross-conserved protein determinants are occluded by self-N-glycan shielding, limiting B cell recognition of the underlying polypeptide surface. The exceptions to the contiguous glycan shield include the conserved receptor CD4 binding site (CD4bs) and glycoprotein (gp)41 elements proximal to the furin cleavage site. Accordingly, we performed heterologous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 66 publications
3
135
0
Order By: Relevance
“…Many different multivalent display strategies have been employed. They include synthetic nanoparticles [26,27], liposomes [28], micelles [29], and polymers [30]. But one of the most common is to display antigens on platforms based on virus-like particles (VLPs).…”
Section: Immune Responses Elicited By Multivalent Vaccinesmentioning
confidence: 99%
“…Many different multivalent display strategies have been employed. They include synthetic nanoparticles [26,27], liposomes [28], micelles [29], and polymers [30]. But one of the most common is to display antigens on platforms based on virus-like particles (VLPs).…”
Section: Immune Responses Elicited By Multivalent Vaccinesmentioning
confidence: 99%
“…The particles from the 2D classes do not reconstruct into an interpretable 3D density when provided a closed and ligand-free trimer as the initial model, which is likely a result of trimer dissociation (classes represent free protomers with several Fabs bound), trimer opening, or a combination of both. At least two broadly-neutralizing antibodies have been reported that induce trimer dissociation by targeting gp41, 3BC315 (derived from natural human infection) (47), and 1C2 (derived from rabbit immunization with engineered Env) (48). It has also been reported that antibodies directed against the CD4 binding site, V3 loop and the MPER can induce gp120 shedding (49).…”
Section: Evidence Of Destabilization Of Sosip Trimer Conformation By mentioning
confidence: 99%
“…Vaccine efforts against different targets from the erythrocytic stage of P. falciparum and also from gametocytes for transmission-blocking purpose are also being actively investigated [3]. Alternatively, delivery of antigens via attachment to liposomes is also being pursued for multivalent display of, for example, HIV-1 envelop trimers, where ease of production and ability to attach different antigens make these flexible platforms for antigen delivery, representing strategies yet to be explored for malaria [4][5][6][7]. Currently, the most advanced vaccine candidate is a recombinant protein based on the central NANP repeats and C-terminal region of the Pf circumsporozoite protein (GlaxoS-mithKline RTS,S/AS01 vaccine) [8].…”
Section: Introductionmentioning
confidence: 99%